Buckling of Framed Domes - Buchert, Kenneth P. (Engineering Journal, 1965)
The use of steel framed domes has increased considerably in recent years. Domes of the order of 1,000 ft in base diameter are now being designed for sports stadiums and other large structures where it is desirable to cover large open areas. As the size of domes increases, general buckling analysis becomes an important part of the design. The recent failure of a 307 ft diameter dome in Bucharest has caused dome designers to make a careful analysis of their design for buckling.